Activation of immune defences against parasitoid wasps does not underlie the cost of infection - Leitão, Alexandre B.; Geldman, Emma M.; Jiggins, Francis M. (Frontiers in Immunology, 2023)
Parasites reduce the fitness of their hosts, and different causes of this damage have fundamentally different consequences for the evolution of immune defences. Damage to the host may result from the parasite directly harming its host, often due to the production of virulence factors that manipulate host physiology. Alternatively, the host may be harmed by the activation of its own immune defences, as these can be energetically demanding or cause self-harm. A well-studied model of the cost of infection is Drosophila melanogaster and its common natural enemy, parasitoid wasps. Infected Drosophila larvae rely on humoral and cellular immune mechanisms to form a capsule around the parasitoid egg and kill it. Infection results in a developmental delay and reduced adult body size. To disentangle the effects of virulence factors and immune defences on these costs, we artificially activated anti-parasitoid immune defences in the absence of virulence factors. Despite immune activation triggering extensive differentiation and proliferation of immune cells together with hyperglycaemia, it did not result in a developmental delay or reduced body size. We conclude that the costs of infection do not result from these aspects of the immune response and may instead result from the parasite directly damaging